An Overview of Nutritional Composition and Potential Health Benefits of Moringa sp. - Asma Saghir Khan; Nazish Zulfiqar (Advanced Research in Biological Science Vol. 9, 2024)
Moringa, scientifically known as Moringa oleifera, is a multipurpose tree that has gained considerable attention due to its exceptional nutritional and medicinal properties. Native to the Indian subcontinent, Moringa is now cultivated in various tropical and subtropical regions worldwide. This article provides an overview of the nutritional composition and potential health benefits of Moringa, highlighting its role as a valuable resource for combating malnutrition and addressing various health conditions. Moringa leaves offer multiple health advantages, including antioxidant activity, anti-microbial activity, anti-cancerous activity, anti-inflammatory action, and many more. Hypertension, diabetes, heart failure, and several pathological situations are the cause of this oxidative stress. Natural antioxidants are always the first choice of consumers and are better than synthetic antioxidants resistance strain incidences of pathogens increase, resulting in higher death rates worldwide, and new and improved antimicrobial drugs must be developed. In this regard, medicinal plants are coming into the limelight, having a superior approach to health and being devoid of synthetic pharmaceutical side effects. The anticancer activity of Moringa leaves aqueous extracts was investigated against human hepatocellular carcinoma HepG2 cells. A significant reduction (44–52%) was seen in HepG2 cell growth when the leaf extracts were orally administered, making them potent anticancer agents. The information presented here is based on a review of relevant research articles available on Google Scholar.